Authentic Leadership and Innovation: What is the Role of Psychological Capital? - Novitasari, Dewiana; Siswanto, Edy; PURWANTO, AGUS; Fahmi, Khaerul (IJOSMAS, 2020)
This research aims to measure the effect of authentic leadership style and psychological capital on the innovative work behavior of a manufacturing company in Indonesia. Psychological capital also plays a role as a mediation between the relationship between authentic leadership and innovative work behavior. Data collection was carried out by simple random sampling to the 303 population. The returned and valid questionnaire results were 231 samples. Data processing was using the SEM method with SmartPLS 3.0 software. The results of this research are authentic leadership style and psychological capital have a positive and significant effect on innovative work behavior. Psychological capital as a mediator for the relationship between authentic leadership style and innovative work behavior. This novel research is proposing a model to enhance innovative work behavior among employees of a manufacturing company in Indonesia through authentic leadership practice and psychological capital. This research can pave the way to improve employee readiness in facing global business competition.